Kinetics of high temperature oxidation of end-of-life Ni/Cu/Ni coated NdFeB rare earth permanent magnets. (15th August 2021) - Nababan, Deddy C.; Mukhlis, Reiza; Durandet, Yvonne; Pownceby, Mark I.; Prentice, Leon; Rhamdhani, M. Akbar
Highlights: The oxidation kinetics of EOL NdFeB magnet at 973−1473 K in air were investigated. The oxidation was controlled by a diffusion mechanism following the Ginstling–Brounshtein model. The overall activation energy was calculated to be 168 kJ/mol. The coating on the magnet was found to negatively affect the kinetics of the oxidation. Abstract: The oxidation behaviour of rare earth permanent magnets contributes significantly to the understanding and efficiency of their high temperature recycling processes. The current paper evaluated the high temperature oxidation kinetics of end-of-life Ni/Cu/Ni coated NdFeB rare earth permanent magnets at 973−1473 K under ambient air conditions. The general microstructure observations and kinetics measurements showed that the oxidation was controlled by a diffusion mechanism that followed the Ginstling–Brounshtein model. The overall activation energy was calculated to be 168 kJ/mol. Results suggest that the presence of a Ni/Cu/Ni coating has a negative effect, reducing the overall kinetic rates by ten times.